Science frontiers : Vol. 5 : 1946 to the present - Spangenburg, Ray; Moser, Diane Kit (New Delhi : Viva Books, 2006)
Contributed papers presented at a seminar on the history of science and society in Indian context.
Includes bibliographical references.
Keywords: Science -- India -- History -- Congresses